Pruritic urticarial papules and plaques of pregnancy: An unusual case report from a tertiary care hospital of the Eastern part of India - Mahapatra, Soumyadeep; Maiti, Anindita (Asian Journal of Medical Sciences, 2024)
Pruritic urticarial papules and plaques of pregnancy (PUPPP) is a rare dermatitis of unknown etiology first diagnosed in 1979. It occurs most commonly in the 3rd trimester of pregnancy. Postpartum presentation is extremely rare. Treatment modalities mostly involve the relief of symptoms. We are going to report here one case of a 24-year-old primigravid female who presented in the 9th month of the gestational period with generalized pruritic eruptions in a tertiary care hospital in the Eastern part of India. These eruptions were erythematous, hyperpigmented, and papular, which began within the striae distensae of the abdomen and progressively spread on the skin of upper and lower limbs, trunk, and buttocks. After the delivery of a full-term male child, there was an aggravation of the symptoms such as itching and disturbed sleep. There was also increased spread of the lesions over the skins of the mentioned areas, which persisted for 6 weeks of the postpartum period. The lesions and associated symptoms gradually subsided with topical application of corticosteroids and hydroquinone along with oral antihistaminic for prolonged periods. Our objective behind reporting this case is to make clinicians aware of PUPPP as a differential diagnosis of peripartum and postpartum pruritic eruptions for prolonged periods.